Autism Reflected in Jodi Picoult's House Rules (2010): A Psychoanalytic Approach - Akbareti, Devi, Dr. Phil. Dewi Candraningrum, M.Ed (2016)
This study aims to describe how to understand people who have Asperger‟s syndrome. An effort to become a person in general who communicate and interact to start a friendship. How to educate and address the person who has Asperger‟s syndrome, and constraints are reflected in the novel House Rules by Jodi Picoult. In this novel will also be shown how important the role of parents in the life and the depth of affection of a mother who fights for her child. This research is a qualitative descriptive study carried out under the framework of psychoanalytic theory. This research uses Jodi Picoult‟s novel entitle House Rules as a data source. Some words, phrases, and dialouge is used as the primary data. This study shows that Jacob as a child who has Asperger‟s syndrome with confronted problem, namely; his ambition to analyze an event that made him suspect as a search for and uncover Jess to make her death in prison. Jacob also facing obstacles such as; social interactions, depression, autism. It inhibits to be like others.